Veterans as Teachers? A Literature Review of Inhibitors and Enablers for Veterans to Complete College and Veterans as Teachers. - Brandon Moore (Arizona State University, 2015)
With almost two million veterans returning from Afghanistan and Iraq, many of them may be coming to American colleges and universities as a result of the Post-9/11 GI Bill. These veterans have lucrative education benefits available to them, such as the Montgomery GI Bill, Post-9/11 GI Bill and, if they joined from Texas, the Hazlewood Exemption. With the shortage of teachers in high-needs schools and in areas of need, such as math and science, veterans provide a population from which to draw teachers. Research on military veterans becoming teachers indicates that they exhibit the characteristics sought in effective teachers. This literature review provides a short history of veterans education benefits, reviews the inhibitors and enablers for veterans to complete college, and reviews the literature on veterans as teachers.  This literature review informs the discussion of policy on campuses as well as decisions that are made.